Relationship between religiosity and resilience in breast cancer survivors - Mutya Puji Nur Rachman; Irfan Fahmi; Nisa Hermawati (Psikologia : Jurnal Psikologi, 2018)
Breast cancer survivors feel stressed and weak when receiving a verdict, but not a few of them are able to rise up and submit to God that they will be cured. The results aims to determine the relationship between religiosity and resilience in breast cancer survivors. The method is bivariate correlational. Subject of this study is 35 breast cancer survivors of Bandung Cancer Society. The measuring instrument were the Religiusity Scale and Resilience Scale. The results showed that religiosity with resilience in breast cancer survivors has a positive relationship with a correlation value of 0.597 or moderate level of correlation, coefficient of determination is 0.356 or 35.64%. Religiosity aspects that have the highest contribution value are forgiveness aspects with a contribution value of 0.913, and the aspect of resilience which has the highest contribution value in increasing resilience is the aspect of work engagement with a contribution value of 0.917.